CURRENT STATE OF POPULATION OF GAME MAMMALS HABITING SHELKOVSKOY DISTRICT OF CHECHNYA AND WAYS FOR OPTIMIZATION - A. M. Batkhiyev; H. S. Yandakrhanov (Юг России: экология, развитие)
Aim. The goal of the research is that: to identify the taxonomic composition of game species and make full list of species to assess the current state of populations and resources to carry out eco-faunistic analysis of the distribution of game mammals habiting Shelkovskiy district of Chechnya. Methods. We used mapping techniques, various methods of census forms and scientific processing of the collected material, systematic and bioecological analysis. Results. As a result, we have identified 5 ecological complexes and characterized them by distribution on the identified and described natural habitats. We have made an inventory of species, identified conditions of rare species and determined their status. Biometric data has been obtained for a number of species; their biological and ecological features have been described. We also identified the species composition of game mammals and their spatial distribution of habitats. The differentiation of species in ecological groups has been carried out. Data has been obtained on the number of nine major types for the period of 2012-2013, and their characteristics. We have made an estimation of ecological and economic potential of resources of game mammals of the study area. Conclusions. Based on the analysis of the results we can make a judgment about the level of biodiversity of species of game mammals of the studied area, the current state of their number and possible use for commercial, sports and recreational purposes. We propose specific measures such as the use of existing biological resources i.e. species of mammals, as well as the creation of new protected areas as a form of preserving and increasing the number of mammals in the area. The research results can be useful for monitoring and creating specially protected natural reservations, protection of endangered species. The findings have implications for the organization of hunting economy to increase the number of game animals.